K-Ras and cyclooxygenase-2 coactivation augments intraductal papillary mucinous neoplasm and Notch1 mimicking human pancreas lesions - Chiblak, Sara; Steinbauer, Brigitte; Pohl-Arnold, Andrea; Kucher, Dagmar; Abdollahi, Amir; Schwager, Christian; Höft, Birgit; Esposito, Irene; Müller-Decker, Karin (Scientific reports, 2016)
Mutational activation of K-Ras is an initiating event of pancreatic ductal adenocarcinomas (PDAC) that may develop either from pancreatic intraepithelial neoplasia (PanIN) or intraductal papillary mucinous neoplasms (IPMN). Cyclooxygenase-2 (COX-2)-derived prostaglandin E2 (PGE2) is causally related to pancreatic carcinogenesis. Here, we deciphered the impact of COX-2, a key modulator of inflammation, in concert with active mutant K-RasG12D on tumor burden and gene expression signature using compound mutant mouse lines. Concomitant activation of COX-2 and K-RasG12D accelerated the progression of pancreatic intraepithelial lesions predominantly with a cystic papillary phenotype resembling human IPMN. Transcriptomes derived from laser capture microdissected preneoplastic lesions of single and compound mutants revealed a signature that was significantly enriched in Notch1 signaling components. In vitro, Notch1 signaling was COX-2-dependent. In line with these findings, human IPMN stratified into intestinal, gastric and pancreatobillary types displayed Notch1 immunosignals with high prevalence, especially in the gastric lesions. In conclusion, a yet unknown link between activated Ras, protumorigenic COX-2 and Notch1 in IPMN onset was unraveled.
Gesehen am 30.04.2020